Exploring Turkish preservice teachers' mental models of the environment: Are they related to gender and academic level? - Ahi, Berat; Balcı, Sibel; Alisinanoğlu, Fatma (Informa UK Limited, 2017)
ABSTRACTThe current study aimed to establish Turkish preservice teachers' mental models of the environment and to determine the relationship these models have with gender and grade level. The study group comprised 463 Turkish preservice teachers from primary school education and preschool education departments. The data from the study were collected from drawings made by the participants. The drawings were evaluated using the Draw-an-Environment Test Rubric (DAET-R). The results of the study revealed that preservice teachers provide only superficial and scientifically deficient descriptions of the environment and that they constructed their mental models by perceiving the environment not as a unity of systems but as an object. On the basis of the findings, which showed that many preservice teachers do not include humans in their drawings, or draw biotic factors without other elements, it was concluded that preservice teachers perceive the environment as “nature” only. Although no statistically significant...
Keywords: Mental Model; DAET; Drawing; Environment; Qualitative Analysis; Preservice Teacher; 4. Education; 3. Good health